The importance of Indigenous and local people for cataloging biodiversity - Copete, Juan C; Kik, Alfred; Novotny, Vojtech; Cámara-Leret, Rodrigo (Trends in ecology & evolution, 2023)
Indigenous and local peoples' (ILPs) role in cataloging life on Earth has been significant but underappreciated. ILPs knowledge faces growing cultural and biological threats. Greater participation by ILPs in research would make science more efficient, conservation more sustainable, and traditional knowledge stronger, but formidable obstacles remain.
Keywords: Biodiversity; biodiversity discovery; zachování přírodních zdrojů; znalosti; traditional knowledge; interdisciplinary research; Humans; equitable science; conservation; biodiverzita; Conservation of Natural Resources; lidé; Knowledge